Educational Tourism Destination Readiness and Opportunities of a State University - Canson, Maria Cristina I.; Caelian, Merlita V. (Philippine Social Science Journal, 2022)
A state university can be a tourist destination since it possesses the A’s of tourism in addition to its engagement in teaching and conduct of research. Thus, this descriptive-comparative research investigated the readiness of a Philippine state university as an educational tourism destination. It used a researcher-made questionnaire to assess the presence of attractions, accessibility, accommodation, activities, amenities, and accountability or the 6As from the perspective of 262 internal and external stakeholders. It also identified opportunities for the promotion and enhancement of tourism resources. Results show that the state university is very ready as a tourism destination in terms of the 6As. It means it highly possesses the resources, components, and conditions needed to operate as a tourism destination. The resources recommended for promotion are farm and nature attractions. The majority of opportunities for enhancement are in accessibility.